-1
$\begingroup$

The problem is to solve the separable differential equation $\sqrt{xy}~~\frac{dy}{dx}=\sqrt{4-x}$.

My work thus far: $ \sqrt{xy}~~ {dy}=\sqrt{4-x}~~dx \\ \sqrt{y}~~ {dy}=\sqrt{\frac{4-x}{x}}~~dx \\ \int \sqrt{y}~~ {dy}= \int \sqrt{\frac{4-x}{x}}~~d x \\ \frac{2}{3} y^{3/2} =\int \sqrt{\frac{4-x}{x}}~~dx \\ \frac{2}{3} y^{3/2} =\int \sqrt{\frac 4 x - 1 }~~dx $

The right side is a difficult integral to evaluate.

Is there an easier approach I have missed, or should I persist in trying to solve the integral.

$\endgroup$
2
$\begingroup$

Hint: Apply the substitution $u=\frac{4}{x}$, then integrate by parts and then again look for a clever substitution to get to the form $\int\frac{1}{t^2+1}dt=arctan(t)$.

$\endgroup$
1
$\begingroup$

Hint Sometimes an integral $\int \sqrt{f(x)} \, dx$ can be resolved by rearranging $u = \sqrt{f(x)}$ to give a reverse substitution (where we may need to restrict the domain of $f$).

In our case, setting $u = \sqrt\frac{4 - x}{x}$ and rearranging and differentiating yields the substitution $$x = \frac{4}{u^2 + 1}, \qquad dx = -\frac{8 u\, du}{(u^2 + 1)^2},$$ which gives $$\int \sqrt\frac{4 - x}{x} dx = -8 \int \frac{u^2 \,du}{(u^2 + 1)^2} .$$ The latter integrand is rational and so can be solved with standard techniques.

The occurrence of the form $u^2 + 1$ in the denominator suggests the substitution $u = \tan \theta$, $du = \sec^2 \theta\, d\theta$.

$\endgroup$
1
$\begingroup$

Make the substitution $t = \sqrt{x}$, then

$$ \int 2\sqrt{4-x}\ \frac{dx}{2\sqrt{x}} = \int 2\sqrt{4-t^2}\ dt $$

This is a standard trig substitution. Let $t = 2\sin \theta$

\begin{align} \int 2\sqrt{4-t^2}dt &= \int 2\cdot 2\cos\theta\cdot 2\cos\theta\ d\theta \\ &= \int 8 \cos^2\theta\ d\theta \\ &= \int 4(1+\cos2\theta)\ d\theta \\ &= 4\theta + 2\sin2\theta + C \end{align}

Going backwards

\begin{align} 4\theta + 2\sin2\theta + C &= 4\theta + 4\sin\theta\cos \theta + C \\ &= 4\arctan\frac{t}{2} + t\sqrt{4-t^2} + C \\ &= 4\arcsin\frac{\sqrt{x}}{2} + \sqrt{x}\sqrt{4-x} + C \end{align}

$\endgroup$
0
$\begingroup$

Thankyou to the tips given. I will attempt to answer my question. $$ \sqrt{xy}~~\frac{dy}{dx}=\sqrt{4-x} \\ \sqrt{xy}~~ {dy}=\sqrt{4-x}~~dx \\ \sqrt{y}~~ {dy}=\sqrt{\frac{4-x}{x}}~~dx \\ \int \sqrt{y}~~ {dy}= \int \frac{ \sqrt {4-x}}{\sqrt x}~~dx \\ \frac{2}{3} y^{3/2} =\int \frac{ \sqrt {4-x}}{\sqrt x}~~dx \\ \text{ Make the substitution u = √x } \\ \frac{2}{3} y^{3/2} = 2\int \sqrt { 4- u^2} du \\ \\ \text{ Substitute w = u/2 } \\ \frac{2}{3} y^{3/2} = 8 \int \sqrt{ 1 - w ^2} ~dw \\ \text{ using trig substitution} \\ \frac{2}{3} y^{3/2} = 4 w \sqrt {1 -w^2}+4 \arcsin \left( w \right) + C \\ \text{back substituting } \\ \frac{2}{3} y^{3/2} = 4 \frac u 2 \sqrt {1 -\left( \frac u 2 \right) ^2}+4 \arcsin \left( \frac u 2 \right) + C \\ \frac{2}{3} y^{3/2} = 2 \sqrt x \sqrt {1 -\left( \frac {\sqrt x }{ 2} \right) ^2}+4 \arcsin \left( \frac {\sqrt x }{ 2} \right) + C \\ \frac{2}{3} y^{3/2} = 2 \sqrt x \sqrt {1 -\left( \frac {x}{4} \right)}+4 \arcsin \left( \frac {\sqrt x }{ 2} \right) + C \\ \frac{2}{3} y^{3/2} = 2 \sqrt x \frac{ \sqrt {4 -x }}{ \sqrt{4} } +4 \arcsin \left( \frac {\sqrt x }{ 2} \right) + C \\ \frac{2}{3} y^{3/2} = \sqrt x \sqrt {4 -x } +4 \arcsin \left( \frac {\sqrt x }{ 2} \right) + C \\ y^{3/2} =\frac{3}{2} \left( \sqrt x \sqrt {4 -x } +4 \arcsin \left( \frac {\sqrt x }{ 2} \right) + C \right) \\ y^{3/2} = \left( \frac{3}{2} \sqrt x \sqrt {4 -x } + 6 \arcsin \left( \frac {\sqrt x }{ 2} \right) + \frac 3 2 C \right) \\ y = \left( \frac{3}{2} \sqrt x \sqrt {4 -x } + 6 \arcsin \left( \frac {\sqrt x }{ 2} \right) + C \right) ^{2/3}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.